Pengaruh Beban Operasional dan Pendapatan Operasional (BOPO) terhadap Return On Asset (ROA) pada PT. Bank Rakyat Indonesia (persero), TBk periode 2007-2012 - Atikah Atikah (Universitas Muhammadiyah Jambi, 2013)
The various aspects that affect the development of a bank, can be assessed qualitatively because each element contain a variety of interrelated aspects and interplay with one another. Having regard to the development of financial statements can be obtained from portrayal of good to poor circumstances or financial position of a bank.Profit the company described the compensation that may be available to employees.The company's ability to generate profits indicate that there is a flow of cash coming in.It would be one of the reasons external parties to be able to invest their funds. Ability to obtain one of them reflected on the magnitude of the value of the Return On Assets in a Bank, where his great abilities are one of the factors that affected the operational performance of banking is one of the comparative cost of quantity is the charge indicators will operanional and operating income (BOPO). During the period 2007-2012 ROA PT Bank Rakyat Indonesia (persero), TBk. ROA PT Bank Rakyat Indonesia (persero), TBk appropriate fluctuates but with a trend to decline, while in the same period BOPO also fluctuates but with the trend to increase. BOPO and ROA influence negatively with great influence of coefficient of 0.012 meaning. If BOPO increase the ROA will decrease, which each increased 1% BOPO will cause ROA declined by 0.012%.